Soil Bacterial Community in the Multiple Cropping System Increased Grain Yield Within 40 Cultivation Years - Chen, Tao; Hu, Ruiwen; Zheng, Zhongyi; Yang, Jiayi; Fan, Huan; Deng, Xiaoqiang; Yao, Wang; Wang, Qiming; Peng, Shuguang; Li, Juan (Frontiers in Plant Science, 2021)
The shortage of land resources restricts the sustainable development of agricultural production. Multiple cropping has been widely used in Southern China, but whether the continuous planting will cause a decline in soil quality and crop yield is unclear. To test whether multiple cropping could increase grain yield, we investigated the farmlands with different cultivation years (10–20 years, 20–40 years, and >40 years). Results showed that tobacco-rice multiple cropping rotation significantly increased soil pH, nitrogen nutrient content, and grain yield, and it increased the richness of the bacterial community. The farmland with 20–40 years of cultivation has the highest soil organic carbon (SOC), ammonium nitrogen, and grain yield, but there is no significant difference in the diversity and structure of the bacterial community in farmlands with different cultivation years. The molecular ecological network indicated that the stability of the bacterial community decreased across the cultivation years, which may result in a decline of farmland yields in multiple cropping system> 40 years. The Acidobacteria members as the keystone taxa (Zi ≥ 2.5 or Pi ≥ 0.62) appeared in the tobacco-rice multiple cropping rotation farmlands, and the highest abundance of Acidobacteria was found in the farmland with the highest SOC and ammonium nitrogen content, suggesting Acidobacteria Gp4, GP7, GP12, and GP17 are important taxa involved in the soil carbon and nitrogen cycle. Therefore, in this study, the multiple cropping systems for 20 years will not reduce the crop production potential, but they cannot last for more than 40 years. This study provides insights for ensuring soil quality and enhancing sustainable agricultural production capacity.